Effect of Component and Total Mixed Ration Feeding Systems on In Situ, In Vitro Degradability of Ground Filter Paper, and Ruminal pH in Dairy Bulls - Barros, A.; G. F. Guadayo; C. C. Sevilla; J. A. N. Bautista; J. T. Dizon; M. M. Loresco; R. A. B. Narag; A. A. Angeles (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
The study was to evaluate the effect of feeding systems on the in situ and in vitro degradability of ground filter paper substrate and ruminal pH level. The experiment used three cannulated dairy bulls. In a 2×2 crossover design, three replications were carried out for every incubated sample. Cattle were fed COMP and TMR feeds twice a day in 2 different treatment groups. The substrate cellulose of Whatman No.1 filter paper was incubated in the rumen fistulated dairy bulls. Rumen fluid samples were collected after 3 hours of morning feeding with a total of 100 mL sampled every 1 h for 24 h. The pH of the rumen fluid was determined using a calibrated pH meter at each sampling interval. The result of the in situ ruminal degradation of the DM, NDF, and ADF at 3, 6, 12, 24, 48, and 72 h was not significantly different. The in vitro gas production volume and fermentation kinetics at each time set were not significantly different. Rumen fluid pH values were not significantly different. However, the TMR group had a higher determination coefficient of 90% than the COMP group, which had 70%. Overall, COMP and TMR feeding did not affect the ruminal degradability capacity of DM, NDF, and ADF in situ techniques. Neither COMP nor TMR feeding affected in vitro gas production. However, those feeding systems can influence microbial activity in the rumen, where TMR has an advantage in maintaining and stabilizing pH levels in the fermentation and digestion of feeds in the rumen.